Design and implementation of electronic control system for UTM-AUV - Saat, Ezril Hisham Mat; Mamat, Rosbi; Yaakob, Omar (ieee, 2000)

(untitled)
Parallel development of autonomous underwater vehicle (AUV) mechanical hardware and electronic control system can be effectively carried out if the control system can be independently developed from the mechanical hardware. Real time simulation using personal computer (PC) could be an alternative for fast development of control system. This paper describes an approach to design the electronic control system for UTM-AUV. Analysis of the designed control system has been done in real time simulation by using Real-Time Workshop. The generic real time has been selected as system target file to provide real time simulation environment. This concept used a stand-alone PC running the designed control system, which can be assumed as the actual AUV. At the same time another PC, which running the Simulink is connected to the stand-alone PC via TCP/IP connection to view the behavior of the control system